Cultivating the paradigm of disruptive innovation: Knowledge production in a transdisciplinary field under a cocitation analysis. (11th August 2021) - Shu, Cheng; Sun, Sunny Li; Zeng, Xiaodan
Abstract : This paper aims to gain an impression of recent developments in the field of disruptive innovation and to analyse changes in the intellectual structure of this field from 1994 to 2014 using bibliographic methods. Applying "Mode 2" transdisciplinarity knowledge production and paradigm development theory, we perform a citation and cocitation analysis with multidimensional scaling tools using the Web of Science as the data source. Through the analysis, we present major research trends as well as the evolution of paradigm development in the transdisciplinary field of disruptive innovation. We also find that the conversation between theory and practice and the pollination from divergent sources are critical to the advancement of disruptive innovation.